2012
DOI: 10.1038/oby.2012.27
|View full text |Cite|
|
Sign up to set email alerts
|

Escalating Coverage of Obesity in UK Newspapers: The Evolution and Framing of the “Obesity Epidemic” From 1996 to 2010

Abstract: Obesity is one of the fastest growing and most serious public health challenges facing the world in the 21st century. Correspondingly, over the past decade there has been increased interest in how the obesity epidemic has been framed by the media. This study offers the first large-scale examination of the evolution and framing of the obesity epidemic in UK newspapers, identifying shifts in news coverage about the causal drivers of and potential solutions to the obesity epidemic. Seven UK newspapers were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 18 publications
7
116
3
7
Order By: Relevance
“…This supports previous research which has shown that when reporting cancer research and research into diet--related conditions such as cardio--vascular disease and obesity, media coverage tends to focus responsibility disproportionately on the individual rather than framing the issue as the responsibility of the state or civil society (Lawrence, 2004, Hilton et al 2012, Hellyer and Haddock--Fraser 2011, Clarke and Everest 2006. In addition a health geography perspective was lacking in the coverage of this research despite the volume of work linking place and space to health (Kearns, 1993;Brown and Duncan, 2002;Cummins et al 2007) and evidence showing a differentiation in bowel cancer incidence between northern and southern parts of the UK (Cancer Research UK, 2016) as well as a small association between deprivation and incidence of bowel cancer for men (Cancer Research UK, 2016).…”
Section: Discussion: Responsibilising Eaters Through the Mediasupporting
confidence: 85%
See 1 more Smart Citation
“…This supports previous research which has shown that when reporting cancer research and research into diet--related conditions such as cardio--vascular disease and obesity, media coverage tends to focus responsibility disproportionately on the individual rather than framing the issue as the responsibility of the state or civil society (Lawrence, 2004, Hilton et al 2012, Hellyer and Haddock--Fraser 2011, Clarke and Everest 2006. In addition a health geography perspective was lacking in the coverage of this research despite the volume of work linking place and space to health (Kearns, 1993;Brown and Duncan, 2002;Cummins et al 2007) and evidence showing a differentiation in bowel cancer incidence between northern and southern parts of the UK (Cancer Research UK, 2016) as well as a small association between deprivation and incidence of bowel cancer for men (Cancer Research UK, 2016).…”
Section: Discussion: Responsibilising Eaters Through the Mediasupporting
confidence: 85%
“…I seek to extend this argument by applying this concept of geographies of responsibility to the way responsibility for diet is placed and framed in newspaper coverage of nutrition research into bowel cancer and by examining whether the UK news media reinforces an individualistic approach in its coverage of diet--related cancer prevention research. This has already been shown to be the case for obesity, type--2 diabetes and coronary heart disease, where media coverage has been shown to focus responsibility for these diet--related conditions disproportionately on the individual rather than framing the issue as the responsibility of the state, industry or civil society (Lawrence, 2004, Hellyer and Haddock--Fraser 2011, Hilton et al 2012. Similarly, research into media coverage of cancer also identified frequent and overt individualistic framing of cancer as opposed to offering a community perspective Everest, 2006, Clarke andvan Amerom 2008).…”
Section: Nutrition and Geographies Of Responsibilitymentioning
confidence: 98%
“…Various reasons for the widespread reporting obesity stigma and discrimination have been offered. However, a constantly cited vehicle is media portrayal with increasing evidence to demonstrate that obese people are the target of fat jokes and derogatory portrayals [22][23][24][25][26][27][28].…”
Section: Obesity Discrimination In the Workplacementioning
confidence: 99%
“…Major newspapers from the USA, UK and Canada were found to portray lifestyle as the main cause of obesity, suggesting roles for the government, industry and the individual in addressing the epidemic (Ries, Rachul, & Caulfield, 2010). Hilton, Patterson, and Teyhan (2012) also examined UK newspaper portrayal of obesity over a 15 year period from 1996 to 2010. They identified that reports relating to obesity increased over time, that since 2001 they were more likely to be focused on childhood obesity, that portrayals were more likely to report on causal that non-causal factors, and, that a high proportion commented on solutions for obesity.…”
Section: Introductionmentioning
confidence: 99%